Sustaining e-learning studies in higher education: an examination of scientific productions in Scopus between 2019 and 2021 - Gao, Yanjun; Wong, Su Luan; Md. Khambari, Mas Nida; Noordin, Nooreen; Geng, Jingxin (Multidisciplinary Digital Publishing Institute, 2022)
The study aimed to gain a comprehensive picture of current e-learning development in higher education. In order to do this, research questions including distribution patterns, contributors in terms of journals, authors and countries, as well as theme development and evolution pattens of e-learning were proposed. To address the research questions, a bibliometric analysis was carried out by reviewing 877 peer-reviewed journal publications published from 2019 to 2021 in the Scopus database, with the help of Biblioshiny and VOSviewer software. The results indicated a fast annual growth in the number of publications from 2019 to 2021, with social science as the core subject area for e-learning development. Sustainability (Switzerland) and Education and Information Technologies were the most contributing journals, due to their high citation numbers and productivity. China, Malaysia, and Saudi Arabia made the highest contributions to the e-learning field in terms of the publication numbers and citation indicators. “Acceptance factors”, “perceptions”, “mental health”, “teachers”, “university students”, and “e-learning management and organization” were interest topics discussed between 2019 and 2021. More empirical research was featured to address the issues of e-learning in 2019, and the research interests focused on motivation, administration, and pedagogical aspects. Meanwhile, from 2020–2021, it was observed that themes such as machine learning, artificial intelligence, and information and communication technology in the e-learning field were booming. The study provided extensive insight into the existing publications of the e-learning landscape; accordingly, the results could be useful to researchers, policymakers, and practitioners in this field.